Peranan Pemerintah Dalam Mempercepat Pertumbuhan Ekonomi di Kota Batam - Alia Anggita Paramasari; Wahjoe Pangestoeti; Viona Pramesty Eka Putri; Dela Afrilia (Lembaga Pengembangan Kinerja Dosen, 2024)
One of the important factors in financial improvement is Economic Development. The task of the government in an effort to achieve effective progress is to decide the direction of the improvement arrangement and to realize the goal of this progress requires a large improvement arrangement to realize stable financial development in order to advance the welfare of society is to expand Small and Medium Enterprises and Labor. It aims to find out the concurrent impact and half impact of Small and Medium Enterprises and Labor on the financial development of Batam city. An economy is said to be developing if the level of economic accomplishment measures achieved today is higher than that achieved in the previous period. Development is achieved if the physical amount of goods and administrations created in the economy increases over a long time. The reason of this research is to see and encourage for the impact of Investment and Local Revenue (PAD) on Economic development. Methods used in this research This research uses literature review to get an overview of what are the efforts of Batam city government in economic growth in Batam city, therefore in this article there are various data sources and references. The data used in this research is additional information in the form of budget reports obtained from BP Batam and BP Batam's official website. The result of this research is a review of several data sources that have been collected for the purpose of solving the problem at hand derived from previous studies and research.